Effects of Chemical Heat Sink Generated by an Oxalic Acid Cooling Stream on Film-Cooling Effectiveness. Issue 1 (2nd January 2016) - Cheng, K.; Liang, S.; Huai, X.
Abstract : Based on the theory of heat transfer enhancement, a novel film-cooling method for turbine blades that involves a chemical heat sink generated by the use of oxalic acid as a cooling stream has been proposed. Experiments were conducted on a flat plate with a row of 30° angled holes, and the conventional method using air as the cooling stream was examined for comparison. Overall, the results of this study demonstrate that the proposed cooling method involving an oxalic acid-induced chemical heat sink is more effective than the conventional method.